2012
DOI: 10.3109/02688697.2012.690911
|View full text |Cite
|
Sign up to set email alerts
|

A fully thrombosed giant posterior inferior cerebellar aneurysm mimicking an intracranial tumour in a child

Abstract: This report presents a fully thrombosed giant aneurysm of the posterior inferior cerebellar artery (PICA) mimicking an intracranial tumour in a 9-year-old paediatric patient. Surgical clipping and aneurysmectomy were performed. Postoperative imaging studies confirmed the removal of the lesion and the patient was discharged with no neurological deficits. Our case shows that giant thrombosed aneurysms involving the PICA could be potentially misdiagnosed as neoplasms in children and great care must be exercised w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Burkhardt et al demonstrated ruptured PICA aneurysm was an independent risk factor of abducens nerve palsy 59 . Giant aneurysms might be misdiagnosed as tumors of posterior fossa due to similar symptoms and imaging features which were sometimes indistinguishable even with magnetic resonance angiography (MRA) and digital subtraction angiography (DSA) 46 , 47 . Computed tomography angiography (CTA) is insensitive to the distal PICA aneurysms resulting from the thin lumen of PICA.…”
Section: Aneurysmmentioning
confidence: 99%
“…Burkhardt et al demonstrated ruptured PICA aneurysm was an independent risk factor of abducens nerve palsy 59 . Giant aneurysms might be misdiagnosed as tumors of posterior fossa due to similar symptoms and imaging features which were sometimes indistinguishable even with magnetic resonance angiography (MRA) and digital subtraction angiography (DSA) 46 , 47 . Computed tomography angiography (CTA) is insensitive to the distal PICA aneurysms resulting from the thin lumen of PICA.…”
Section: Aneurysmmentioning
confidence: 99%
“…It is the result of hematogenous spread from a primary focus in the lung [ 12 ]. In clinical field, it is not so rare to misdiagnosed thrombosed aneurysm as a brain tumor, however, thrombosed aneurysms mimicking intracranial neoplasm have been reported only in 4 cases previously ( Table 1 ) [ 13 , 14 , 15 , 16 ]. It might be because it seems not so valuable to report.…”
Section: Discussionmentioning
confidence: 99%
“…But, in this case, it seemed valuable to share, because as mentioned above, it was not so big as giant aneurysms and the location of aneurysm was lenticulostriate artery which is rare. Among the other reported cases, the aneurysms of 2 cases [ 13 , 16 ] were included in a category of giant aneurysm and the aneurysms of 3 cases [ 13 , 14 , 16 ] were located in posterior circulation. Every patient of the reported cases was managed successfully by controlling the parent arteries and totally removing the thrombosed aneurysm, and the outcomes were excellent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been rare reports where completely thrombosed aneurysms have imitated neoplasms based on initial presentation and imaging. [ 9 11 12 17 24 ] Though up to 40% of cerebral aneurysms involve the middle cerebral artery,[ 4 16 ] no cases have been reported along the middle cerebral artery. Here, we describe a patient with seizure activity where serial contrast-enhanced MRI brain studies demonstrated a persistent rim-enhancing lesion with surrounding fluid-attenuated inversion recovery (FLAIR) signal concerning for a neoplastic process.…”
Section: Introductionmentioning
confidence: 99%